Enhancing Digital Competencies in Education: A Comprehensive Framework for Teacher Training and Leadership - Aliyah, Adah; Mahmud, Mahmud; Arifin, Bambang Samsul; Nursobah, Asep (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
The development of digital platform-based education requires teachers not only to master technology but also to design interactive, contextual, and pedagogically valuable digital learning experiences. This study aims to create a digital training framework to accelerate the professional growth of Islamic Religious Education teachers by integrating TPACK and Four-D. This study uses a qualitative case study approach. Data were collected through training observations, in-depth interviews, and documentation, then analyzed interactively. The results show that the increase in data-based competencies includes Canva media creation (85%), PowerPoint presentations (81%), Wordwall and Quizizz digital assessments (78%), Padlet collaboration (74%), Google Classroom class management (72%), and digital teaching simulations (69%). This study develops a Digital Training Leadership Framework grounded in practice, collaboration, digital projects, and the dissemination of teacher work, as a new contribution. The implications of this study recommend designing digital training based on dominant practices, continuous mentoring, and peer mentoring to strengthen the digital learning Leadership of Islamic Religious Education teachers.